Socialization Applicant Tracking System (ATS) and ATS Curriculum Vitae for ITL Trisakti and General Students - Marlita, Devi; Handayani, Sri; Perwitasari, Erni Pratiwi; Azis, Muhammad Ridwan; Hamonangan , Yosua (Asian Journal of Community Services, 2024)
The method used for the program is through socialization and knowledge sharing about the Applicant Tracking System (ATS) in the form of case examples and tips online because the implementation of the events was still in the PPKM period. The Implementation of the activity was centered at ITL Trisakti, East Jakarta and participants could take part online. The purpose of the socialization is to prepare basic knowledge for students and the general public about ATS and its derivative applications. As a result of these activities, participants understand more about ATS. And start updating their profiles and curriculum vitae using ATS so that it is more accessible to recruiters of companies that need employees to fill the required positions.